Cross-country differences in the effect of political connections on stock price informativeness - KUSNADI, Yuanto (Institutional Knowledge at Singapore Management University, 2018)
Using aninternational sample of firms from 28 countries, we document that there existsa negative relationship between political connections and the informativenessof stock price, as measured by idiosyncratic volatility (IV). This finding isrobust to alternative regression specifications, sub-samples analyses, andconcerns related to endogeneity. A more detailed analysis shows that out of thedifferent types of possible connections, the connectedness of the owners is theprimary driver of this result. Further, the negative association is onlysignificant for firms in countries characterized by low institutional quality(i.e. corrupted countries, countries with low access to external equitymarkets, and countries with low media penetration). There is no evidence of anyrelation between political connections and stock price informativeness forfirms in countries characterized by high institutional quality. Overall, our results show that although politicalconnections exacerbate rent-seeking that weaken the firms’ informationenvironments on average, the negative information consequences are compensatedby the countries’ institutional quality.